Islamic Health Protection Retirement plan for Malaysian employees : an investigation from a behavioral approach - Chowdhury, Mohammad Abdul Matin (Kulliyyah of Economics and Management Sciences, 2021)
The ageing population has become a crucial concern around the world. Based on the Department of Statistics Malaysia (2020), Malaysia is experiencing a sharp growth in the ageing population- leading to an ageing nation. The public pension scheme is notably inadequate due to its low replacement ratio, while employees provident fund (EPF) exhibits lower savings of participants. This research aims to propose an Islamic health protection retirement plan (i-HPRP) for Malaysian employees, followed by exploring retirees' experiences, investigating the influential factors to the suggested model's preferences, and the moderating effect of age on the hypotheses' relationship. This research has applied sequential mixed methodology consist of qualitative and quantitative; thematic analysis was applied for qualitative, structural equation modelling for quantitative analysis. A total of 28 interviewees for semi-structured interviews, six participants in focus group discussion and 498 survey data were used in this research. The findings from qualitative analysis exhibited that most retirees were not prepared for retirement. The proposed i-HPRP was supported by the takaful practitioners understudy, especially on the fund contribution from two sources: employee and employer. A total of six independent variables from life-cycle theory and social exchange theory were adopted to investigate the relationships with the preferences towards i-HPRP model. The quantitative findings showed the significant role of saving behaviour, future planning and commitment to the preferences towards i-HPRP. In contrast, perceived benefit, spending behaviour did not exhibit a significant effect and trust showed a significant negative relationship. Meanwhile, age significantly moderated the relationship between savings, perceived benefit, future planning, commitment, and preferences towards i-HPRP. The findings of this research would be significant for takaful operators and related government agencies to design an innovative health retirement plan that may assist future retires regarding future financial preparation and protection.